Analytical characterization of bible and textiles artifacts from sinope balatlar church excavations for conservation purposes - ÖZOMAY, MERAL; ÖZOMAY, ZAFER (My University, 2022)
© 2022. This is an open-access article distributed under the terms of the Creative Commons Attribution License. Archaeological textile and paper materials shed light on cultural studies in different fields. In this study, a composite textile material and 2 printed Biblical artifacts of the 19th c., found during the excavation of the Balatlar Building Complex were investigated. The building complex, also known as the Balatlar Church or Mithridates Palace, is an imperial hamam complex belonging to the Roman Period, located in the Ada Street of Sinope province in the north of Turkey. It was found that different materials such as metal yarn, paper used under embroidery, and decorative beads used on textile material were used in the textile fragment recovered from tomb VIII of the Balatlar Building Complex. The investigation concerned the fiber types and dyestuffs for textile material, paper types and dyestuffs used for biblical artifacts by using non-destructive and microa-nalysis methods for these unique heritage objects. Attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), Optical microscope (OM), Digital Microscope (DM), Scanning Electron Microscopy with Energy Dispersive X-Ray Analysis (SEM-EDX) and High-Performance Liquid Chromatography-Diode Array Detector (HPLC-DAD) was used. It was determined that the textile find consists of two different fabrics, the main fabric, and the lining, and the dye that gives the main fabric its red color is the root dye (Rubia tinc-torum L.). Also, Alizarin and madder (Rubia tinctorum L.) was determined as a plant source. It has been estab-lished that only the pattern threads are silk threads. HPLC-DAD chromatograms has been analyzed of paper pieces of the, written and unwritten sides, paper-board and leather sides archaeological L.(Large) Bible and S. (Small) Bible books. It was concluded that natural dyestuffs were not used in the production of the paper and leather parts of the L.Bible and S.Bible books. For the written text Iron (III)-gallic acid binary complex vibration bands were detected. Documentation and research studies conducted on 2 discovered Biblical artifacts have shown that biological degradation has oc-curred on the surface of the artifact. As a result of microscopic examination, it was found that the cover part of the L.Bible was made of cardboard and there were remnants of gray side paper. Remnants of leather-pre-pared binding were found on the surface of S.Biblical artifact.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Antropoloji; Arkeoloji ve Sanat Tarihi; Social Sciences and Humanities; History; Anthropology; Archaelogy and History of Art; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; ANTROPOLOJİ; ARKEOLOJİ; TARİH; Arts & Humanities (AHCI); ARTS & HUMANITIES; ANTHROPOLOGY; ARCHAEOLOGY; HISTORY; Koruma; Sosyal Bilimler ve Beşeri Bilimler; Arkeoloji (sanat ve beşeri bilimler); Arkeoloji; Conservation; Social Sciences & Humanities; Archeology (arts and humanities); Archeology; archaeological books; archaeological textile; ATR-FTIR; Bible; composite artifacts; gallic acid; HPLC-DAD; ink; SEM-EDX; composite artifacts; archaeological textile; archaeological books; Bible; ATR-FTIR; HPLC-DAD; SEM-EDX; gallic acid; ink